Perinatal and neonatal mortality rates and causes of death at Marmara University Hospital - (:unkn) unknown (My University, 2001)
Objective: The aim of our study was to establish the stillbirth, early and late neonatal mortality and perinatal mortality rates at Marmara University Hospital and to compare the rates with those of other countries. Methods: We evaluated the mothers who gave birth at Marmara University Hospital and their infants prospectively for two years from January 1998 to January 2000. The causes of perinatal deaths were grouped according to the modified Wigglesworth Classification. Maternal risk factors were ascertained. Results: The stillbirth rate was 15.1%, early and late neonatal mortality rates were 3.8% and 2.8% respectively, and the perinatal mortality rate was 18.8% in our hospital. The mean gestational age of the neonates who died perinatally in the perinatal period was 26.8±1.2 weeks. In this group, 68% of the mothers did not receive any antenatal care. Sixty percent of their mothers were primipar and 40% were multipar. The most common cause of death was hypoxia during the intrauterine period and preterm labor and delivery. The total number of deliveries in our hospital was 1060 in two years and 19% of the mothers had high risk pregnancy. The average number of preterm delivery was 37 (7.9% of all deliveries) per year of which 13 (2.5%) had a birth weight of less than 1500 grams. Conclusion: The perinatal mortality rate at our hospital (18.8%) is lower than that of the world (53%) but higher than the rate of the developed countries (10%). The perinatal mortality rates of the other hospitals in Turkey are between 11.9- 108%. Systematic antenatal care should be applied all around the country, high risk pregnancies should be managed at the tertiary care hospitals with intensive care units and the number of neonatal intensive care unit beds should be increased.
Keywords: Antenatal care; Neonatal mortality rate; Perinatal mortality rate